2002
DOI: 10.3171/foc.2002.12.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Two-level anterior cervical discectomy and cage-assisted fusion without plates

Abstract: Object Anterior cervical discectomy (ACD) is an effective and safe treatment for nerve root or spinal cord compression caused by disc herniation or spondylosis. Cervical interbody fusion allows preservation of the physiological lordosis and stability of the cervical spine. Based on data reported in the literature, fusion rates decrease significantly when more than one level undergoes surgery, and some authors recommend the addition of a plate system to improve result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
0
14
0
5
Order By: Relevance
“…There were no significant differences between the two groups (p = 0.12, α = 0.05). The mean preoperative painDETECT score for the group of patients with subsidence was 13.3 (10-21), falling to 13.1 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in mean time of follow-up 1 and 12.6 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in mean time of follow-up 2. In the group of patients without subsidence, the mean Figure 4 Cervical spine (female, 66 years) with spinal stenosis in C5/6 and C6/7 and myelopathy treated by cervical cages in C5/6 and C6/7 -X-rays taken A immediately postoperatively, B 1 year after surgery without cage subsidence, and C 3 years postoperatively with osseointegration without subsidence.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…There were no significant differences between the two groups (p = 0.12, α = 0.05). The mean preoperative painDETECT score for the group of patients with subsidence was 13.3 (10-21), falling to 13.1 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in mean time of follow-up 1 and 12.6 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in mean time of follow-up 2. In the group of patients without subsidence, the mean Figure 4 Cervical spine (female, 66 years) with spinal stenosis in C5/6 and C6/7 and myelopathy treated by cervical cages in C5/6 and C6/7 -X-rays taken A immediately postoperatively, B 1 year after surgery without cage subsidence, and C 3 years postoperatively with osseointegration without subsidence.…”
Section: Resultsmentioning
confidence: 94%
“…Although the VAS indicated no significant improvement from before surgery to mean time of follow-up 1 (p = 0.09, α = 0.05) or between the two follow-ups, a significant improvement was noted between the preoperative VAS and mean time of follow-up 2 (p = 0.006, α = 0.05). On the painDETECT questionnaire, the total cohort scored 11.4 (mean; 4-21) preoperatively, which increased slightly in mean time of follow-up 1 to 11.8 (7-26) before dropping again in mean time of follow-up 2 to 10.9 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). There were no significant improvements.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings showed that application of fusion after cervical discectomy helps improving preoperative alignment problems; however, ACD without fusion may cause new-onset alignment problems probably because of narrowing of the disc space. It was reported that abnormal movements due to these alignment issues may also cause adjacent segment problems (7,13,16,(18)(19)(20)(21)(22)(23) p<0.001). Those study results suggested that the primary cause of adjacent segment disease may be natural progression of cervical spondylosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 However, titanium cages prevent adequate radiographic visualization of fusion and raise concerns regarding stress shielding of the bone. 11 Carbon fiber-reinforced polymer (CFRP) cages, which are radiolucent and have a modulus of elasticity closer to bone to prevent stress shielding, have been shown to achieve high fusion results of 93% to 100% without plating [12][13][14][15][16][17][18] when intraoperative, intervertebral distraction was used. Lower fusion rates were noted when surgery was performed without distraction.…”
mentioning
confidence: 99%